Ecological health - Gislason, Maya K. (Advances in medical sociology ;, 2013)
Drawing on ecosystem thinking, complexity and postnormal science, Ecological Health offers a radical new way of thinking about the health issues of the 21st Century. This volume reflects on recent social scientific engagement with Ecosystem Health research and practice and sets out a vision for the future. While significant links between human health and the environment are increasingly evident, how to make sense of the interdependence of human health on natural systems is posing significant challenges. Ecological health is a new approach used by medics, public health practitioners, veterinarians, as well as social and natural scientists who study health at the nexus between human, animal and ecological systems. This volume is a reference tool offering a sociological analysis of the interrelationship between society, earth systems and health as conceptual frameworks. The authors provide methodological tools for conducting social science research that integrates social, natural and medical systems. It will appeal to a broad audience of researchers and practitioners who currently work in the arena of ecology and health and as well as those interested in expanding their research.